2011
DOI: 10.1002/jsfa.4619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of technological processing and preservation method on amino acid content and protein quality in kale (Brassica oleracea L. var. acephala) leaves

Abstract: Raw and processed (blanched or cooked) kale leaves are a good source of amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…"Winterbor," and they indicated that chlorophyll content decreased during leaf senescence. Korus (2012) reported total chlorophyll concentrations from 121 mg/100 g for kale. In a study of Italian, Portuguese and Turkish kales, Ferioli et al (2013) suggested that chlorophyll content was affected by sample origin and growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…"Winterbor," and they indicated that chlorophyll content decreased during leaf senescence. Korus (2012) reported total chlorophyll concentrations from 121 mg/100 g for kale. In a study of Italian, Portuguese and Turkish kales, Ferioli et al (2013) suggested that chlorophyll content was affected by sample origin and growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that the chemical reactions undergone by some of the most labile AAs upon processing might have an impact on the digestibility of the extrudates and films. In particular, lysine seemed to be one of the AAs most notably affected by processing, in line with what has been reported in previous studies (Korus, 2012;Mesías et al, 2016). The effect of processing on the microstructure and the distribution of proteins in the two seaweeds was investigated by confocal laser scanning microscopy (CLSM), and representative images are shown in Figure 2.…”
Section: Statisticssupporting
confidence: 86%
“…Several studies have shown that total amino acid content can be affected by cooking conditions. Decreases of 12% and 24% were reported by Korus (2012) in blanched and cooked kale leave samples compared with raw leaves and Lisiewska, Slupski, Skoczen-Slupska and Kmiecik (2009) found that amino acid content in cooked Brussels sprouts was 89-108% of that observed in the raw material. Similarly, the content in green asparagus decreased after blanching and canning, phenylalanine, tyrosine, methionine and valine being the most stable constituents during the treatments (López, Ros, Rincón, Ortufio, Periago, & Martinez, 1996).…”
Section: Resultsmentioning
confidence: 92%